“She is a Spinster”: a Descriptive Study on Perception Toward Single Women - ., Nanik; M.W. Taira, Mareyke; Hendriani, Wiwin (International Journal of Engineering and Technology, 2018)
The aim of this research was to explore perception toward single women, according to respondents from 4 different subject groups. Exploration on topic was intriguing to be further researched, considering that the percentage of single women had been increasing in numerous countries, but the discussion was lacking, especially in Indonesia. Respondents in this study were Indonesian single or married men and women aged 25-70 years. Respondents were gathered through purposive incidental sampling (N = 128) and consisted of 41 single women, 49 married women, 13 single men, and 25 married men. An open-ended questionnaires constructed by the first author was used as measurement tools. Respondents were tasked to mention perceived positive and negative impression toward single women. Data gathered underwent two analysis stages. The first part was a descriptive content analysis and the second stage was a descriptive statistical analysis comparing means from one-way ANOVA. Statistical analysis showed significant result (average p < .05) when comparing means of positive and negative perception based on demographic statistics. Results showed significant negative perception and strong labeling toward single women although there were also significant positive perceptions. Negative and positive perceptions of single women tend to be universal from several generations of adults.
Keywords: Perception; Single Women; Content Analysis